Phenotypic and genotypic characteristics of exopolysaccharide-producing fungi as a source of food additives - Robby Akroman; NURHAYATI NURHAYATI; SONY SUWASONO; JAY JAYUS (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Akroman R, Nurhayati N, Suwasono S, Jayus J. 2019. Phenotypic and genotypic characteristics of exopolysaccharide-producing fungi as a source of food additives. Biodiversitas 20: 2468-2474. As the demand for materials suitable for edible film in food processing is increasing, the exploration of exopolysaccharide (EPS) producing fungi is important. Some fungi had been reported to produce extracellular polysaccharide having rheological properties potential as thickener and or plasticizer useful for edible film raw material. Therefore, this study was focused on isolation and identification of EPS-producing fungi from the plantation area surrounding the University of Jember, Indonesia. The fungal isolate obtained was morphologically identified based on mycelia and spore type, while its genotype was determined using ITS1 and ITS4 primers. The optimum initial culture pH for EPS production was measured using shake flask culture fermentation. The rheological properties of the EPS were determined using Brookfield viscometer, and surface structure of EPS was observed using a scanning electron microscope (SEM). The result showed that the mycelium of the isolate was reddish-brown and septated, its spores were formed as conidiospores. Internal Transcribed Spacer (ITS) sequence of the fungus showed that the isolate is a new species. Therefore, it was designated as C. lunata isolate RJ01. Optimum initial pH for EPS production was pH 6.0, achieved after 5 days fermentation yielded 2.6 g L-1 of EPS. The EPS from C. lunata isolate RJ01 have no cytotoxic activity on vero cell. The rheological behaviour of C. lunata EPS was viscous, and its surface structure of EPS was compact indicating its potency as thickening agent and plasticizer, a material required for edible film formation in food industries.